A new pleurostomatid ciliate, Amphileptus salignus n. sp. (Protozoa, Ciliophora), from mangrove wetlands in southern China - Chen, Ruimin; Lin, Xiaofeng; Warren, Alan (Zootaxa, 2011)
The morphology and infraciliature of a new brackish water pleurostomatid ciliate, Amphileptus salignus n. sp., collected from mangrove wetlands in southern China were investigated using observations of live cells and the protargol impregnation method. Amphileptus salignus can be separated from its congeners by its large cell size, the presence of 4 left and 24–29 right somatic kineties, two kinds of extrusomes, the number and location of contractile vacuoles, and its habitat.